Implementsi Program Gerakan Literasi Sekolah dalam Meningkatkan Prestasi Peserta Didik Pada Pembelajaran Bahasa Indonesia - Mirfaka, Azam; Rahman, Marita Lailia (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
Gerakan Literasi Sekolah (GLS) is one of program which is elected by the government to face the education of 21th century problems. MI Al-Huda is regarded success to implement GLS with several achievements that is reached in literacy field. Therefore, the aims of this research focused on design of GLS in MI Al-Huda, the implementation of GLS steps in MI Al-Huda, and How GLS influence in increasing the students’ achievement in Indonesian language learning. This research used mixed methods with an exploratory model the research instruments were interviews, questionnaires, and documents. The results of the research indicate that the design of GLS program in MI Al-Huda depends on GLS steps, so the implementation of GLS program there based on every GLS steps. The result of this research also indicates that H0 was rejected and the signification value less than 0.05 by correlation value 0,494 and 0,462. It means GLS program influence in increasing students’ achievement of Indonesian language although includes in medium categorize. The conclusion is design and implementation of GLS program in MI Al-Huda are good enough that success to apply GLS program up to learning step. Besides, GLS program give impact to improve students achievement of Indonesian language learning especially for students at fifth grade in MI Al-Huda Bonggah Ploso Nganjuk.